Hygiene management in newborn individually housed dairy calves focusing on housing and feeding practices - Heinemann, Céline (J Anim Sci, 2020)
In calf rearing, the first weeks of life are critical and associated with the highest mortality due to enteric and respiratory diseases. A well-implemented hygiene management can help to protect calves’ health preventively by reducing the load of pathogenic bacteria and interrupting infection chains. The aim of this study was to identify deficiencies in hygiene management of individually housed dairy calves by surveying current practice and examining feeding and housing equipment with different hygiene indicators. On 11 farms, different locations in 2 pens or hutches for individual calf rearing prepared for restocking and 2 feeding buckets per farm, including the inner and outer surfaces of artificial teats, were visually scored for cleanliness and sampled with swabs (housing equipment: n = 167; feeding equipment: n = 120). The sanitation of floors was tested with sock samples (n = 41). A total of 328 samples were analyzed for adenosine triphosphate (ATP) and protein residues, aerobic total viable count (TVC), total coliform count (TCC), Escherichia coli, methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum β-lactamase-producing bacteria (ESBL), and Salmonella spp. After evaluation of these results, the farmers were informed about the findings and trained on improvement in hygiene management personally. The sampling was repeated after 1 year to detect possible changes in hygiene management. The highest bacterial loads (TVC, TCC, and E. coli) were observed in feeding equipment, especially the inner teat of milk feeding buckets. Environmental samples, primarily the sidewalls and back walls of tested pens and hutches, exhibited the lowest bacterial counts and ATP and protein residues. All samples were negative for MRSA and Salmonella spp. In 10.5% of all samples, ESBL was detected, and in 6.8%, ESBL E. coli was detected, predominately in sock samples, followed by feeding equipment samples. Training in hygiene management showed only limited effects. In conclusion, there is still great potential to improve the implementation of hygiene measures in individual calf housing. In particular, more attention should be paid to the cleaning of feeding buckets and artificial teats, as this is a simple means of interrupting the possible spread of pathogens among calves.